Developing English Language Textbook for Midwifery Students at Institute of Health Science in Sampang, Indonesia - Ika Meilinda Ummul Ma’rufa (University of Surakarta, 2023)
The demand for qualified midwives in their job field encourages the midwifery academy to include the English language as a compulsory subject for the students. It is scarce to find ESP books designed for students of midwifery. This study aims to develop an English language textbook specified for the Midwifery Academy of Sukma Wijaya Sampang students. It was carried out to require the student’s needs and interests. It was conducted using the Research and Development (R & D) design in which the need assessment procedures and expert validation were included. The data collection involved several instruments, namely questionnaires and interview guidelines. The questionnaires were applied to the students and chief of the midwifery department on the need assessment procedure. At the same time, the checklist was given to the experts on the process of product validation. All the data were analysed descriptively. Its advanced English language textbook consists of fourteen chapters which deliver the texts and activities related to the needs of midwifery students. Besides the essential English skill, this developed book also provides some English vocabulary related to the midwifery context. It concluded that the material applied to students; in terms of their attractiveness, appropriateness of the content and difficulty level.